Portfolio optimization using cryptocurrency - Raka Arjunaldi Pramana Putra; Mychelia Champaca (Privietlab, 2026)
This study aims to analyze the role of cryptocurrency investment in optimizing the performance of a portfolio comprising traditional assets, such as stocks, foreign exchange, and gold. This quantitative research employs the Markowitz Mean-Variance Optimization model and Sharpe ratio analysis. The data used consist of monthly closing prices from January 2019 to December 2024 for three cryptocurrencies (BTC, ETH, and XRP), three banking stocks (BBCA, BBRI, and BMRI), three foreign exchange pairs (USD/IDR, EUR/IDR, and GBP/IDR), and gold. A comparison was made between an optimal portfolio without a cryptocurrency and an optimal portfolio with a cryptocurrency. The results indicate that the inclusion of cryptocurrency significantly increased the portfolio's expected return from 14.07% to 32.08%. This increase was accompanied by a rise in risk (standard deviation) from 11.39% to 19.49%. However, portfolio efficiency improved dramatically, as evidenced by the Sharpe ratio surging from 70.89% to 133.83%. In both scenarios, gold consistently played a dominant role as a stabilizing asset in the portfolio. It is concluded that, during the study period, cryptocurrency served as a significant return enhancer and efficiency booster in the investment portfolio.